Acteonidae, Bullinidae and Ringiculidae (Gastropoda: Heterobranchia) from the Plio-Pleistocene of the Philippines - Helwerda, Renate A. (Zootaxa, 2015)
Twenty-three species of Acteonidae, Bullinidae and Ringiculidae are documented from the so-called “Cabarruyan” fauna from the Plio-Pleistocene of Pangasinan, the Philippines. There are eleven species of Acteonidae, one species of Bullinidae and eleven species of Ringiculidae. Seven species are described here as new, these are: Bathyacteon valdesi nov. spec., Bullina virgoides nov. spec., Ringicula bella nov. spec., R. circumscripta nov. spec., R. caelestis nov. spec., R. opima nov. spec. and Microglyphis angulata nov. spec.. The presence of Acteonidae and Bullinidae indicates that polychaete worms were also present.